Effects of process conditions on the heat transfer coefficient at the polymer-mold interface and tensile strength of thin-wall injection molding parts - Zhu, Laiyu; Min, Liping; Li, Xianglin; Zhai, Zhanyu; Drummer, Dietmar; Jiang, Bingyan (Journal of Polymer Engineering, 2019)
Generally, the strength at the weld line of the injection molded part is very weak. The heat transfer coefficient (HTC) between the polymer melt and the mold cavity surface was analyzed to solve this problem. The surface roughness of the mold cavity and the material of the mold insert were changed to adjust the interface environment between the polymer melt and the mold cavity surface. HTC was obtained by combing the experimental measurement with the theoretical calculation. In the current study, the influence of HTC on the tensile strength of the weld line of the molded specimen was investigated. The results show that the weld line strength of the molded specimen increases with the decrease in HTC between the polymer and the mold cavity surface. Meanwhile, the decrease in the surface roughness of the mold cavity or replacing the mold material with lower thermal conductivity can reduce the value of the HTC between the polymer and the mold effectively and can delay the cooling rate of the hot polymer melt. This provides a new idea to solve thin-wall injection molding weld line defects.
CRIS-Team Scopus Importer:2019-05-03
Keywords: heat transfer coefficient; process condition; thin-wall injection molding